Clinicopathological features of nodular gastritis in three classes of age. Issue 6 (16th August 2021) - Kako, Satoko; Iwaya, Yugo; Nagaya, Tadanobu; Hara, Daichi; Okamura, Takuma; Iwaya, Mai; Kurasawa, Shingo; Kato, Sawako; Nakayama, Yoshiko; Akamatsu, Taiji; Umemura, Takeji
Abstract: Background: Nodular gastritis is most often one of the manifestations of Helicobacter pylori ( H. pylori ) infection, which is a risk factor for gastric cancer. This study aimed to determine if the histological characteristics of nodular gastritis differed across classes of age. Methods: We conducted a retrospective analysis of consecutive patients who had undergone esophagogastroduodenoscopy with multiple mucosal biopsies of the stomach between 2003 and 2019 for evaluation of updated Sydney System scores. We analyzed and compared the histological characteristics of pediatric (≤15 years old), young (16–29 years old), and older (≥30 years old) patients. Results: Of the 1321 patients enrolled, 1027 patients (78%) had H. pylori infection, with 214 patients (21%) of them displaying nodular gastritis. Among nodular gastritis patients, mononuclear cell infiltration Sydney System scores in the gastric body were significantly higher in the older group than in the pediatric ( p < .001) and young ( p < .001) groups. Similar results were seen for neutrophil infiltration scores in the gastric body. To clarify the characteristics of older nodular gastritis, we investigated 1056 older patients (66 with nodular gastritis, 754 with atrophic gastritis, and 236 H. pylori ‐negative). The scores for mononuclear and neutrophil cell infiltration in the gastric body were significantly higher in nodular gastritis patients than in atrophic gastritis patients (both p < .001) and patients negative for H. pylori (both p < .001). Conclusions: The inflammatory changes in the gastric body in older nodular gastritis patients were more severe as compared with those in pediatric and young nodular gastritis patients in addition to older atrophic gastritis patients.